The Christian impact on the shaping of the First Republic of Korea, 1945-48: anti-communism or vision for a new nation?. Issue 4 (2nd October 2018) - Kim, Kirsteen; Kim, Sebastian C. H.
ABSTRACT: Although Christianity was a new and small religion in Korea at the time, in 1945–48 Christian politicians and church leaders were prominent in establishing an independent South Korea as the Cold War began. Kang In-cheol and others argue that this was because Christians were prejudiced against communists and acted out of self-interest, and they hold them complicit in the subsequent Korean War. We shall argue that many Christian leaders were willing to work with communists to preserve the unity of the nation but their experience convinced them that communist aims were incompatible with religious freedom and with their own vision of a democratic nation founded on Christian principles. Our argument contributes not only to an understanding of Korean nationalism, but also to the broader literature on the roles of Christianity in democratisation. It reveals the significant influence of Christian actors at this critical juncture in Korean and world history, the impact of which is still being felt today.